Geodetic base preparation for state border demarcation - Ratkevičs, A.; Celms, A.; Kukule, I. (Видавництво Львівської політехніки, 2016)
In any organizing activities for the national boundaries the established works includes as the first – the political agreement processes, which is known as the “delimitation”, and as second subsequent – state border real technical eviction in the current land area, which is called as the «demarcation» and be understand that a crossdiscipline such as Geodesy there are always play an important role. If in the first delimitation phase of measurement accuracy requirements for geodetic data not so important, then in the next demarcation stage the geodetic accuracy of the data already play an important role. This primarily related to the fact that the general politicolegal status in border demarcation phase becomes also as a real physical and technical objects. As in each technical construction or structure it also generates a serious attention to mathematical precision criteria directly in the field of geodesy. Similarly as in the designing and constructions for any engineering object or in forming land properties. In turn, increase the accuracy of the criteria in the field of geodesy, it is always associated with a theoretical and practical position of the geodetic base and its quality. Quality criteria of geodetic base are always linked with the future activities with geodetic data and services provided for the use of project. They are usually set or needs can be satisfied with the already available the base of the structure and the parameters or it is necessary to improve or build from scratch. Engaging in the border demarcation process, the question of the geodetic base is always topical and it is not always a simple solution. The article examines the in Latvian Republic practices gained experience and knowledge on the geodetic substrate preparation, analyzing the current process of demarcation of the Latvia-Russia border cases and previously realized border demarcation works on the other Latvian national borders (Latvia – Estonia, Latvia – Lithuania and Latvia – Belarus). The end result corroboration of the assumption that in all cases the geodetic base of creation is excludable and indispensable measure, which of course can be realized in various technical, technological or conceptual model versions. Also the latest GNSS technology options do not exclude the need for the establishment of such a substrate. Розглянуто досвід практичного використання геодезичної основи для демаркації державного кордону Латвії з сусідніми країнами. Рассмотрен опыт практического использования геодезической основы для демаркации государственной границы Латвии с соседними странами.
Підготовка геодезичної основи для демаркації державного кордону
Подготовка геодезической основы для демаркации государственной границы
Keywords: GPS; GNSS; geodesy; state border demarcation